Pengaruh Antara Efektivitas Knowledge Management Dan Budaya Organisasi Terhadap Kinerja Guru Sekolah Minggu Buddha (SMB) Chong-De Se Sumatera Utara - Ida Ayu Gede Yadnyawati; Muljadi; Erny (Dhammavicaya : Jurnal Pengkajian Dhamma, 2022)
The purpose of this study was to determine the effect of the effectiveness of knowledge management and culture on the performance of Chong-De Buddhist Sunday School (SMB) teachers in North Sumatra. This research uses multiple regression analysis. In this study using a sample using probability sampling technique, with a total sample of 86 respondents. This research uses primary data, data is collected by distributing questionnaires to respondents via google form which is tested with SPSS 20.0 for Windows. The results showed that the effectiveness of knowledge management had a positive effect on the performance of SMB Chong-De teachers in North Sumatra with the resulting correlation coefficient of ry1 = 0.756 and the coefficient of determination of the resulting score r2y1 = 0.571. organizational culture has a positive effect on the performance of SMB Chong-De teachers in North Sumatra with the resulting correlation score coefficient ry2 = 0.658 and the resulting coefficient of determination scores r2y2 = 0.433. The effectiveness of knowledge management and organizational culture have a positive and significant effect on the performance of SMB Chong-De teachers in North Sumatra with the resulting correlation coefficient score of ry1,2 = 0.846 and the resulting coefficient of determination score of r2y1,2 = 0.716. The regression equation in this study is as follows: 1.2 = 40.207 + 0.846X1 + 0.716X2. Based on these results, it is necessary to optimize the performance of policies and regulations to improve the effectiveness of knowledge management and organizational culture.